Stress stability studies and the estimation of lamotrigine in pharmaceutical formulation by validated RP- HPLC method - Shrivastava P.K.; Shrivastavai S.K. (My University, 2025)
The aim of the present work to develop validated RP-HPLC method which determines stress stability and concentration of lamotrigine in pharmaceutical preparation as per ICH guidelines. Separation was performed using Cecil liquid chromatography CE-4100-dual piston pump equipped with 20 μ l loop and variable W/L UV/Vis detector (λ= 306 nm) and phenomenex, (250 X 4.6 mm) Luna 5μ C 18 (2) 100 A Column. Mobile phase consisted of acetonitrile: methanol: 10mM potassium dihydrogen phosphate buffer (pH -7), (20:20:60 v/v) was used. All the system suitability parameter was found within the range. The method was extensively validated for specificity, linearity, accuracy, precision, recovery, limit of quantitation and detection. The lamotrigine was found to be highly labile to alkaline hydrolysis compared to acid. Lamotrigine degradation was associated with rise in a major degradation product at retention time of 5.4 ± 0.05 min. The percent assay of drug was found to be in the range 99.25 -102.75 in pharmaceutical dosage form. © APTI All rights reserved.